Sexual experiences of girls engaged in child marriage: A review of qualitative - Farhah Kamilah; Elyse Maria Rosa (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Child marriage cases appear to occur in children between 15 and 18 years of age. Girls who are forced into marriage show fear of having sex with their husbands because they are foreign to this situation. Previous research has shown that child marriage causes trauma to girls due to forced sexual intercourse. This study aims to explore sexual aspects from the perspective of married girls. This study uses 3 databases PubMed, EbscoHost, and Proquest. The main keywords are